Cesar's way : the natural, everyday guide to understanding and correcting common dog problems - Millan, Cesar. frey50; Peltier, Melissa Jo. (New York : Three Rivers Press, 2006)
Learn what goes on inside your dog's mind and develop a positive, fulfilling relationship with your best friend. "Dog Whisperer" Cesar Millan is America's most sought-after dog-behavior expert, but he is not a trainer in the traditional sense--his expertise lies in his ability to comprehend dog psychology. Tracing his own journey from a clay-walled farm in Mexico to the celebrity palaces of Los Angeles, Cesar recounts how he learned what makes dogs tick. Here, he shares this wisdom. Cesar's formula for a contented and balanced dog seems impossibly simple: exercise, discipline, and affection, in that order. Whether you're having issues with your dog or just want to make a good bond even stronger, this book will give you a deeper appreciation of how your dog sees the world, and it will help make your relationship with your beloved pet a richer and more rewarding one.--From publisher description.
Prologue. A dog's life -- 1. Growing up with dogs : a view from the other side of the border -- 2. If we could talk to the animals : the language of energy -- 3. Dog psychology : no couch required -- 4. Power of the pack -- 5. Issues : how we screw up our dogs -- 6. Dogs in the red zone : dangerous aggression -- 7. Cesar's fulfillment formula for a balanced and healthy dog -- 8. "Can't we all just get along?" : simple tips for living happily with your dog -- 9. Fulfilling our dogs, fulfilling ourselves -- Cesar's glossary of terms -- Recommendations for further reading -- Cesar recommends : organizations to turn to.
Keywords: Dogs -- Behavior; Dogs -- Training; Human-animal communication